JUSTICE DELAYED IS JUSTICE DENIED - Zīle, Jana (Administrative and Criminal Justice, 2017)
Keynote of the publications is an expression of the British politician, William Ewart Gladstone, (1809-1898) “Justice delayed is justice denied”. Effectiveness of fair legal process in Latvia is rather questionable, because the number of suspen- ded hearings in comparison with the number of designated hearings is still high, thereby the court proceedings may continue for years. Settlement of this question often lies not so much in the impro- vement of legislative and normative acts or in adjustment of procedural issues, as in the attitude and legal consciousness of all involved parties. Moreover, the prestige of judiciary and courts in the society depend not only how well- considered and fairly are their decisions, rulings, judgements etc., but also how effective is the work of courts at all. By significant reducing of length of court proceedings, it is necessary to achieve confidence for the people that courts are independent and work to judge a fair justice in a reasonable time. In the publication are expressed opinions on the necessity to adjust the existing legislation with the purpose to minimize the time required for adjudication of various categories of cases.